A novel exonuclease-assisted isothermal nucleic acid amplification with ultrahigh specificity mediated by full-length Bst DNA polymerase. Issue 75 (1st August 2018) - Ye, Xin; Li, Yang; Wang, Lijuan; Fang, Xueen; Kong, Jilie
Abstract : A novel exonuclease-assisted isothermal amplification to amplify and determine nucleic acids very sensitively and with ultrahigh specificity. Abstract : Here, we introduced a novel exonuclease-assisted isothermal nucleic acid amplification (Exo-NAT) utilizing the full-length Bst DNA polymerase combined with a melting curve analysis. This method achieved an ultrahigh specificity with a good detection limit (10 2 copies) in both singleplex and multiplex detection, which was validated by detecting three diarrhea-inducing pathogens, rotavirus A, astrovirus, and adenovirus, in 42 clinical samples.